2021
DOI: 10.1038/s41467-021-22303-z
|View full text |Cite
|
Sign up to set email alerts
|

Landscapes of cellular phenotypic diversity in breast cancer xenografts and their impact on drug response

Abstract: The heterogeneity of breast cancer plays a major role in drug response and resistance and has been extensively characterized at the genomic level. Here, a single-cell breast cancer mass cytometry (BCMC) panel is optimized to identify cell phenotypes and their oncogenic signalling states in a biobank of patient-derived tumour xenograft (PDTX) models representing the diversity of human breast cancer. The BCMC panel identifies 13 cellular phenotypes (11 human and 2 murine), associated with both breast cancer subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 83 publications
4
42
0
Order By: Relevance
“…Some 89% of cells are correctly detected while we estimate a false positive detection rate of ∼10%. The results have also been validated scienti ically elsewhere 12 .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Some 89% of cells are correctly detected while we estimate a false positive detection rate of ∼10%. The results have also been validated scienti ically elsewhere 12 .…”
Section: Resultsmentioning
confidence: 77%
“…Results as analysed using the current IMC pipeline, successfully reveals the spatial distribution of cell phenotypes in xenografts as observed with MC data. The study finds that centroids of each cell cluster computed per PDX model on the MC training data shows a high correlation ( ρ = 0.67) with the corresponding centroid following cell segmentation and classification using the IMC pipeline 12 .…”
Section: Methodsmentioning
confidence: 97%
“…Furthermore, short-term cultures can be generated from PDTXs, called PDTX-derived tumour cells (PDTCs, Fig 1), and these can be used for pre-clinical high-throughput drug screens (Bruna et al, 2016b;Georgopoulou et al, 2021). While establishing PDTXs can be resource intensive, they most closely resemble the original patient tumour and microenvironment, and thus hold the most promise for validating targeted therapies that will have meaningful clinical outcomes.…”
Section: Targeted Therapymentioning
confidence: 99%
“…PDTOs preserve spatial architecture in vitro (Clevers, 2016), and PDTCs are short-term cultures derived from PDTX cells (Bruna et al, 2016b), both of which can be used to evaluate response to drug therapy and genetic manipulation. Single-cell analysis of the genome, transcriptome, proteome and epigenome may offer layers of information for understanding response of tumour cells to drug therapy (Georgopoulou et al, 2021), an advantage over current drug therapy screens that mainly assess only cell viability. profiles of cancer cells in response to treatment (Tognetti et al, 2021).…”
Section: Future Directions In Pre-clinical Drug Screening and Biomarker Discoverymentioning
confidence: 99%
“…All of these are now beginning to produce new biological insights into the organization of tissues in two-dimensions. For example, recent studies using IMC have revealed that the tissue organization in breast cancer is both informed by the subtype of the tumour and correlates with patient outcomes 14,15 .…”
Section: Introductionmentioning
confidence: 99%